DIGITALIZATION AS AN IMPORTANT FACTOR OF LEGALIZATION OF THE SHADOW ECONOMY - Nozim Muminov; Shoira Olimjanova; Akmal Salimov; Tatyana Kim (Research Parks Publishers, 2020)
The article discusses the issues of digitalization of certain types of economic activity in the context of the total use of electronic (Internet) applications. The first type of activity is related to electronic commerce and the problem of paying through physical cards to an individual’s card, which leads to tax evasion by most people involved in this activity. The second type of activity is directly related to the first, and implies the introduction of a “virtual” cash desk in retail trade.